Perancangan Ulang Logo ION Hotel Padang - RISZA MAULIA HARSHA PUTRA, Erfahmi, Yusron Wikarya (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
Target of scheme of ION Hotel logo is design to repeat communicative logo logo purposes and objectives expressing tired company identity. Methodologies which is used in scheme repeat this ION Hotel logo, method analyse SWOT ( Strength, Weakness, Opporunity, Treatment). Pursuant to target of in used methodologies, to be yielded by new logo of unique ION Hotel, drawing and typically able to deputize company identity. Logo which have been made later;then will in application into various product able to support existence of HotelKeyword: Re-design, Logo ION, Hotel.